Utilising collaborative learning strategies with children who use AAC: A pilot online training program for speech-language pathologists. - Boster, Jamie B. (International Journal of Speech-Language Pathology, 2024)
Purpose: Children who utilise augmentative and alternative communication (AAC) have difficulty participating in interactions with peers and speech-language pathologists (SLPs) lack training in the development of activities to specifically target participation. The purpose of the current study was to explore a pilot online training program designed to provide information about the development of collaborative learning (CL) activities to support participation. Method: A single-subject, multiple baseline across six participants in an initial group and a replication group was completed to assess the number of CL elements included in probe responses during baseline, intervention, and maintenance phases. Result: SLPs were highly accurate in their ability to answer multiple choice questions about CL elements (80%–90%); however, the overall effect of the intervention was weak with a Tau-U of 0.48 for the initial group and 0.53 for the replication group. Conclusion: SLPs can begin to develop skills in designing CL activities for children who utilise AAC as a means to support participation and foster social interaction. Future research is necessary to design efficient and effective online training for SLPs.